[Memo from E. J. Battison to S. D. Chilcote and R. Mozingo regarding a report on the preliminary findings of ACIR study on state cigarette smuggling and taxation] (Tufts Archival Research Center, 2007)
Missing Attachments; Memo from E. J. Battison, Tobacco Institute economist, to S. D. Chilcote and Roger Mozingo regarding Robert Klein's report on the preliminary finding of ACIR study on state cigarette smuggling and taxation. Finds study to be overly optimistic. Accuses study of data errors and incorrect trend analysis. Asserts that more attention should be paid to casual smuggling. Attributes most illegal sales to military and Native American sales.